Developing an interactive portion size assessment system (IPSAS) for use with children. (19th May 2013) - Foster, E.; Hawkins, A.; Simpson, E.; Adamson, A. J.
Abstract: Novel methods of assessing dietary intake are required to reduce the participant burden in dietary surveys, improve participation rates and thereby improve the representativeness of the sample and minimise the impact of measuring dietary intake on a subject's food intake during the recording period. One method of reducing the burden placed on participants in recording dietary intake is to replace weighing of foods with estimation of portion size using tools such as food photographs. The interactive portion size assessment system (IPSAS) is an interactive portion size assessment system for use in assessing portion sizes of foods consumed by children aged 18 months to 16 years. The system is computer‐based and is designed to be administered during an interview for a food diary or 24‐h recall. The portion sizes depicted are age‐specific and based on the weights of foods served to children during the UK National Diet and Nutrition Surveys. The system displays digital images of food used to estimate the amount of each food served to the child and the amount of any food left over. Foods are categorised within the system using a three‐tier structure. Twenty‐seven food group icons are used with two further drop‐down menus to select first the food group, then the food category and, finally, the actual food product. Each food is linked to UK food composition codes and all photographs are linked to the weight of the food depicted. Nutritional output is via a companion database. The present study describes the development of the IPSAS and the structure of the system.